A survey on hygienic practices and immunization coverage among 12-59 months old children in urban slum, Barishal, Bangladesh (Asian Journal of Medical and Biological Research, 2022)
Good hygiene and sanitation are essential for the prevention of infectious diseases. Immunization is one of the most important public health interventions to reduce both morbidity and mortality of infectious diseases. Thus, the survey study aimed to determine the status of hygienic practices and assess the immunization coverage among 12-59 months old children in urban slums. A cross-sectional study was conducted among 259 under five children's (12-59 months) in Barisal city, Bangladesh, from June to December 2019 using a structured questionnaire. Data was collected by interviewing the mothers from different slum areas. Chi-squared test and multiple logistic regression models were used to explore the association. Prevalence of good hygiene practices status was 65.3% and fully immunized was 71.4%. Joint family (AOR=0.54; 95% CI: 0.31-0.95; P